Efektivitas Pelatihan Dan Pengembangan Guru Dalam Mencapai Tujuan Pendidikan Yang Unggul - Reni Andryani; Iryanah Iryanah; Irfan Firdaus; Budi Ilham Maliki (Departement of Mathematics Education, 2024)
In light of current needs for educational innovation and creativity, this study seeks to address the issue of how to better equip educators to act as agents of student learning. The study's overarching goal is to help relevant stakeholders including policymakers, educators, and school districts by providing evidence-based insights into how teacher professional development programmes affect student achievement in a high-quality education setting. Using a